1025Social interaction of middle-aged and older people with and without cardiovascular disease in Australia. (2nd September 2021) - Sayeed, Muhammad Shahdaat Bin; Joshy, Grace; Banks, Emily; Korda, Rosemary
Abstract: Background: Social interaction is important for social wellbeing and may be adversely affected in people with cardiovascular disease (CVD). Large-scale evidence on social interaction among older people with versus without CVD is limited. We quantified and compared social interaction in older people with and without CVD. Methods: Survey data (2006-2009) from the 45 and Up Study were linked to hospitalisations data through CHeReL to ascertain CVD status. Four items from the Duke Social Support Index (social-visits/week, telephone-contacts/week, social-group-contact/week, and number of people to depend on) were examined, using generalised linear models to estimate prevalence ratios (PRs) of no social interaction in people with versus without CVD, adjusting for relevant factors, and separately according to CVD subtype and level of physical disability. Results: There were 266, 504 study participants, 21.4% had CVD. People with CVD were 8%, (95%CI: 5-11%), 7% (2-12%), 4% (3-5%) and 7% (3-11%) more likely than people without CVD to have no social-visits/week, telephone-contacts/week, social-group-meetings/week and people to depend on respectively. The magnitude but not direction of results varied by CVD subtype. People with CVD and severe physical functioning limitations were 30-80% more likely than those with neither of these to have no social interaction. Conclusions: Levels of social interaction were slightly lower in people with versus without CVD, but they varied by social interaction items, CVD subtypes, population characteristics and physical disability. Key messages: Management to improve quality of life for people living with CVD should consider the role of physical disability for social connectedness.